Quality Control and Performance of HIV Rapid Tests in a Microbicide Clinical Trial in Rural KwaZulu-Natal - von Knorring, Nina; Gafos, Mitzy; Ramokonupi, Motsei; Jentsch, Ute; the MDP Team (PLOS ONE, 2012)
Background Quality control (QC) and evaluation of HIV rapid test procedures are an important aspect of HIV prevention trials. We describe QC and performance of two rapid tests, Determine™ and Uni-Gold™ used in a microbicide clinical trial in rural KwaZulu-Natal, South Africa. Methods/Results Internal QC of both HIV rapid tests was conducted at the trial site using a Uni-Gold control kit (Uni-Gold™Recombigen® HIV). Both assays produced the expected results for a total of 4637 QC tests. Study participants were tested for HIV at screening and, if enrolled, at regular time points throughout the study. Positive or discordant results were confirmed by a double HIV immunoassay testing strategy at a local laboratory. Overall, 15292 HIV rapid test were performed. Sensitivity and specificity of Determine was 98.95% (95% CI: 97.72–99.61) and 99.83% (95% CI: 99.70–99.91) respectively [positive predictive value (PPV) 97.91% (95% CI: 96.38–98.92)], for Uni-Gold it was 99.30% (95% CI: 98.21–99.81) and 99.96% (95% CI: 99.88–99.99) respectively [PPV 99.47% (95% CI: 98.46–99.89)]. Conclusions The results suggest that a Uni-Gold control kit can be used for internal QC of both Uni-Gold and the HIV-1 component of the Determine rapid tests. Both rapid tests performed proficiently in the trial population.